Analysis of the 21st century world community system global crisis from the perspective of the systems and self-organization theories - I. Yu. Aleksandrova (Вестник университета)
The article identifies and analyzes main determinants of the 21st century world community system global crisis from the perspective of the systems and self-organization theories. The study analyzes specifics of the world community as a complex social dissipative system functioning and development. Main determinants of the world community modern system entry into the bifurcation zone have been identified and analyzed. A comparative analysis of expert forecasts of trends in the 21st century world community system development, presented in the works of V.I. Vernadsky, N.N. Moiseev, S. Huntington, D.L. Meadows, M. Wackernagel, T. Malthus and neo-Malthusians, and United Nations experts, has been carried out. As a result of the study, the conclusions about possible scenarios for developing the 21st century world community system in the bifurcation zone have been formulated.